Mechanical and thermal characterization of a structural polyurethane adhesive modified with thermally expandable particles - Banea, Mariana D. (2015)
Thermally expandable particles (TEPs) are used in a wide variety of applications by industry mainly for weight reduction and appearance improvement for thermoplastics, inks, and coatings. In adhesive bonding, TEPs have been used for recycling purposes. However, TEPs might be used to modify structural adhesives for other new purposes, such as: to increase the joint strength by creating an adhesive functionally modified along the overlap of the joint by gradual heating and/or to heal the adhesive in case of damage. In this study, the behaviour of a structural polyurethane adhesive modified with TEPs was investigated as a preliminary study for further investigations on the potential of TEPs in adhesive joints. Tensile bulk tests were performed to get the tensile properties of the unmodified and TEPs-modified adhesive, while Double Cantilever Beam (DCB) test was performed in order to evaluate the resistance to mode I crack propagation of unmodified and TEPs-modified adhesive. In addition, in order to investigate the behaviour of the particles while encapsulated in adhesives, a thermal analysis was done. Scanning electron microscopy (SEM) was used to examine the fracture surface morphology of the specimens. The fracture toughness of the TEPs-modified adhesive was found to increase by addition of TEPs, while the adhesive tensile strength at yield decreased. The temperature where the particles show the maximum expansion varied with TEPs concentration, decreasing with increasing the TEPs content.